2008
DOI: 10.3923/pjbs.2008.2331.2335
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Manganese Contents of Soils and Wheat Plants (Triticum spelta) in the Cukurova Region of Turkey

Abstract: In this study, the statistical analysis of manganese contents for soil, leaf and grain samples of the wheat plants, Triticum spelta, in the Cukurova Region of Adana in Turkey was performed to determine the relationship among the variables and correlation coefficients of manganese (Mn) contents. The soil samples were taken from the plant rhizosphere. Leaf samples at the stem elongation time and grain samples at the physiological maturity stage were analysed for Mn contents. The Mn contents of soil (MnS) were be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
2
6
1
Order By: Relevance
“…Tuncay et al (2016) reported that amounts of organic matter (OM) in Cukurova soils were in the range of 0.11-2.76%. Also, Irmak and Vapur (2008) found that OM in Cukurova soils was in the range of 1.46-2.33% that was similar in the SOC results of present study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Tuncay et al (2016) reported that amounts of organic matter (OM) in Cukurova soils were in the range of 0.11-2.76%. Also, Irmak and Vapur (2008) found that OM in Cukurova soils was in the range of 1.46-2.33% that was similar in the SOC results of present study.…”
Section: Resultssupporting
confidence: 90%
“…Soil pH was slightly alkaline and in the range of 7.98-8.18 and no significant differences were found among all soils. But Irmak and Vapur (2008) reported that soil pH in Cukurova region was ranged from 7.50-7.99. Field capacity of soils was in the range of 29.92-36.69% and was not changed significantly between control and sesame soils in each sampling period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zn deficiency is more common in soils with high phosphorous concentration or excessively fertilized with phosphorus (Cakmak et al 2010). Irmak et al (2008) reported severe Zn deficiency in the soils of Cukurova region. The field experiment revealed that both soil and foliar applications of Zn significantly increased yield and 100-seed weight of peanut.…”
Section: Economic Analyses Of Zinc Rates and Fertilization Methodsmentioning
confidence: 99%
“…Peanut is widely produced in Cukurova Region of Southeastern Turkey, and micronutrients' deficiency symptoms are common due to high pH, lime and low organic matter content of the soils (Irmak et al 2008). Thus, this study aims to determine the effect of various amounts and types of Zn application on peanut's yield production along with fat and protein content in high pH and calcareous soils Cukurova Region of Turkey.…”
Section: Inroductionmentioning
confidence: 99%